Accurate and efficient analysis of the upward heat flow in InGaP/GaAs HBTs through an automated FEM‐based tool and Design of Experiments. (28th November 2018) - d'Alessandro, Vincenzo; Catalano, Antonio Pio; Codecasa, Lorenzo; Zampardi, Peter J.; Moser, Brian
Abstract: This paper presents an extensive analysis aimed at quantifying the impact of all the key technology parameters on the upward heat flow in state‐of‐the‐art InGaP/GaAs heterojunction bipolar transistors (HBTs) for various emitter areas and shapes. Extremely accurate thermal simulations are conducted in a relatively short time with a tool relying on a commercial 3‐D finite‐element method (FEM) solver and an in‐house routine for automated geometry construction, optimized mesh generation, sequential solution, and data storing/processing. Design of Experiments is used to define a thermal resistance model as a function of the aforementioned parameters on the basis of a few FEM data.